Pengembangan Modul Elastisitas dan Hukum Hooke Berbasis Guided Inquiry untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Yesi Oktaviani; Ahmad Harjono; Wahyudi Wahyudi (Kappa Journal, 2022)
This study aims to produce a product in the form of a guided inquiry-based module that is feasible, effective and pratical to use. The design used in this study is 4D model consisting of define, design, develop and disseminate. Data collection techniques used validation sheets, critical thinking skills test instruments and student response questionnaires to the module. The validity data were analyzed by determining the CVI for the module by an expert validator. The result of CVI analysis for guided inquiry-based modules by expert lecturers is 1 which is in the very good category, while the results of CVI analysis by practitioners is 1 which is in the very good category. The pretest and posttest data were analyzed to determine the improvement of students’ critical thinking skills through the n-gain test. The results of data analysis obtained an average n-gain of 0.54 with a moderate category which indicates an increase in critical thinking skills. Based on the results of the questionnaire analysis of student responses to the module, it shows positive criteria with an average acquisition of 86.1%. These results can be concluded that the product developed is very feasible, effective and pratical to use in learning